Total Total Quality Management, Transformation Towards Quality and Competitive Madrasah - Zahratun Naemah (Civiliza Publishing, Indonesia., 2025)
This study aims to analyze the application of total quality management (tqm) in realizing quality and competitive madrasas by highlighting the basic principles, implementation strategies, and challenges faced. The background of the research departs from the need for madrasas to improve quality and competitiveness in the midst of the demands of globalization without ignoring Islamic values. The research method used is library research by examining various literature related to TQM, education management, and the concept of quality in Islam. The results show that TQM principles such as customer focus, engagement of all elements, continuous improvement, and data-driven decision-making, are aligned with Islamic values such as ishlah (improvement) and itqan (rigor). Implementation strategies include strengthening quality culture, improving educator competence, stakeholder participation, and implementing transparent and data-based evaluations. However, the implementation of TQM still faces challenges, including limited human resources, inadequate infrastructure, and organizational culture that tends to be bureaucratic. In conclusion, the implementation of TQM in Islamic educational institutions has great potential to improve quality and competitiveness, as long as it is supported by visionary leadership, shared commitment, and consistency in building a culture of quality.